The Impact of Technological Advancement on Unemployment in Turkey - Alfred, Chibuikem Dibor; Seraj, Mehdi; Ozdeser, Huseyin (Global Economics Science, 2024)
Technological advancements have been reshaping industries and economies worldwide. As technology evolves, questions arise about its impact on employment. This study aims to investigate the relationship between technological advancement and unemployment over the period from 1991 to 2020. The objective of this research is to examine the influence of various factors, including Patent Assistance (PA) residents, Gross Domestic Product per capita (GDPpc), Gross Capital Formation (GCF), and the Consumer Price Index (CPI), on the unemployment rate (UEMP). We seek to understand these variables’ long-term and short-term effects on unemployment. We utilized data from the World Bank for our analysis. The study employed the Auto Regressive Distributed Lag (ARDL) methodology to explore the dynamics between technological advancement and unemployment. This method allows us to investigate both short-term and long-term relationships. Our analysis revealed interesting insights. In the long run, we observed that GCF and CPI negatively influenced unemployment, indicating that an increase in these variables is associated with a reduction in unemployment. However, PA had a positive impact on UEMP, although this effect was not statistically significant. In the short term, GCF, GDPpc, and CPI all had a negative effect on UEMP. These findings carry important policy implications. They suggest that fostering startups and entrepreneurial ventures can drive technological innovation and job creation. To support this, policymakers should focus on creating an enabling environment for startups by reducing bureaucratic barriers, streamlining business registration processes, and providing financial and mentoring support. Encouraging entrepreneurship has the potential to unleash innovative ideas, create new ventures, and generate employment opportunities, particularly for the youth population.